Neural dynamics of central–peripheral transition in Chinese handwriting: insights from EEG evidence. - Yin, Yulong; Cai, Xiao; Zhang, Qingfang (Language, Cognition & Neuroscience, 2026)
Previous studies established that handwriting production involves central and peripheral processes, but the transition mechanism between central and peripheral processes remains unclear. To elucidate this transition, we employed a priming paradigm integrating writing video primes with picture naming writing tasks while recording electroencephalogram (EEG) during Chinese character writing. Orthographic processing represents a critical stage of central processing immediately preceding peripheral processing, while peripheral processing involves motor processing. We manipulated orthographic processing by varying the orthographic relatedness between prime and target characters, and motor processing by altering writing direction. Cluster-based permutation analyses revealed a main effect of orthographic relatedness at 320–390 ms, an interaction with writing direction at 474–494 ms, and main effects of writing direction at 516–536 ms and 712–734 ms. These findings empirically support a sequential central-to-peripheral transition during Chinese character handwriting, revealing three successive stages, namely orthographic processing, orthographic-motor interaction, and independent motor processing.